Results of postoperative binocular visual function for infantile esotropia - Makino, Shinji; Hozawa, Kozue; Sakai, Rieko; Kawasaki, Tomoko; Yamamoto, Hiroko; Kurosawa, Hiromi; Nishimura, Kayoko; Hanaoka, Reiko (JAPANESE ORTHOPTIC JOURNAL, 1999)
We studied binocular visual function for infantile esotropia in 74 patients follow-up at least 4 years after surgery. Age on the initial visit ranged from 3 months to 6 years (mean=1.4 years), preoperative angle of esodeviation ranged from 25 prism diopters (PD) to 90 PD (mean=53.4 PD). Initial surgeries were performed ranged from 9 months to 13.5 years (mean=3.3 years). Among the 65 patients (87.8%) wore prisms glasses and Fresnel membrane prisms before surgery. Final ocular alignment were 42 patients (56.7%) with orthophoria, 11 (14.9%) with less than 10 PD, 2 (2.7%) with less than 20 PD, 6 (8.1%) with more than 21 PD and 13 (17.6%) changed postoperative extropia. We examined binocular visual function using a Major Amblyoscope, Bagolini striated glasses test, Worth 4 dots test and Titmus stereo test. Simultaneous perception with normal retinal correspondence was obtained in 66 patients (89.2%). Binocular visual function were obtained in 54 patients (93.1%) at Bagolini striated glasses test and in 44 patients (95.7%) at Worth 4 dots test, respectively. On the other hand, stereopsis was obtained in 9 patients (39.1%). We thought that it is important to maintain orthophoria with prisms glasses in daily life for achieving good binocular visual function.